1050. Hepatitis C Infection amongst People who Inject Drugs (PWID): Injection Practices and Risk Factors. (31st December 2020) - Sankar, Nityasri; Murray, Kim; Burris, Debra D; Thakarar, Kinna
Abstract: Background: The rapidly progressing U.S. opioid epidemic has led to an increased prevalence of infections associated with injection drug use (IDU), such as Hepatitis C (HCV). Previous studies have identified a lack of screening, prevention, and treatment of HCV, which has contributed to an increase in HCV-related mortality. Transmission has been linked to unsafe injection practices. Our study aims to characterize risk factors associated with Hepatitis C (HCV) exposure amongst people who inject drugs (PWID) in Maine, a state heavily impacted by the opioid epidemic. Methods: Data was obtained from a cross-sectional study of participants hospitalized with an IDU-associated infection at four hospitals in Maine identified as high-risk for HIV/HCV outbreaks. The Audio Computer-Assisted Self-Interview survey and medical record review were used to collect data. The components from the BIRSI 7-item score were used to assess the use of safe injection practices. HCV exposure was defined as HCV antibody positive and/or self-reported exposure. Analysis was performed using descriptive analyses and univariate regression modeling. Results: Of the 101 participants enrolled, n=76 (75%) were identified as having exposure to HCV. Out of participants exposed to HCV, 57% reported homelessness (p=< 0.01). Participants exposed to HCV were more likely to have bacteremia during hospitalization (25%, p=.02). All participants unexposed to HCV perceived low likelihood of contracting HCV due to injecting (p=.01). Seventy-one percent of people exposed to HCV reported infrequent use alcohol pads prior to injecting (p=< 0.01) and 67% reported infrequent hand-washing (p=.09). Participants with a higher BIRSI-7 score had higher odds of exposure to HCV (OR=1.48, 95% CI 1.10-2.04). Conclusion: The data obtained highlights significant relationships between HCV exposure and certain risk factors. Homelessness was found to be associated with HCV exposure, suggesting an opportunity for more targeted intervention within this subgroup of PWID. Unsafe injection practices as measured by the BIRSI-7 score were related to HCV exposure, indicating educational opportunities about safe injection practices. Overall, targeted harm reduction services could be beneficial in the screening and prevention of HCV exposure amongst PWID. Disclosures: All Authors : No reported disclosures